Screening and degradation characteristics of a tylosin-degrading strain - Chang-qing FENG; Deng-miao CHENG; Yao FENG; Wei-ning QI; Zhen-hu JIA; Louise WEAVER; Yuan-wang LIU; Zhao-jun LI (Journal of Integrative Agriculture, 2020)
Antibiotics residues have been accumulating in the environment day by day due to overuse of antibiotics. Recalcitrant antibiotic residues, such as tylosin (TYL), can cause serious environmental problems, which makes it important to eliminate TYL from the environment. It is important to eliminate TYL from the environment. In this study, a strain was isolated and purified from fermentation by-product that came from a TYL production factory. The TYL degrading strain was identified by its morphology, physiological and biochemical reactions and sequencing the PCR-amplified fragments of its 16S rDNA-coding genes. The temperature, shaking speed, initial TYL concentration, pH and inoculum sizes were investigated under simulated conditions by using single factor tests. The results showed that TYL2, a high efficient strain was isolated and was identified as Brevibacillus borstelensis. The degradation rate of TYL by this strain could reach to 75% with an initial concentration of 25 mg L−1 within 7 days under conditions of 7% B. borstelensis (v/v, 2×108 CFU mL−1) at pH 7.0 and at 35°C. It is interesting that this strain has a very strong ability to degrade the TYL in natural sewage with the degradation rate of 65% within 7 days. This result could be helpful for the degradation of TYL and provide guidance for the degradation of other antibiotics.